A Cytogenetic Study of the Effect of Bee Venom on the Genetic Material in the Laboratory Mice (Journal of Pharmaceutical Negative Results, 2022)
Bee venom (BV) therapy was used to treat various diseases. It is a tiny essential peptide with a powerful hemolytic feature composed of a known series of amino acids. Since melittin is a non-specific cy¦tolytic pe¦ptide attacking lip¦id m¦embranes which contribute to toxicity, it is suspected that it could have important therapeutic benefits. This study aims t¦o use a multi-biomarker approach to assess the cytogenotoxic ef¦fects o¦f melittin i¦n periph¦eral blo¦od lym¦phocytes of mice and th¦e mole¦cular mechan¦isms invol¦ved. Control and treatment groups are divided into one hundred and fifty mice. Bee venom has been combined with four separates dose of melittin in the peritoneal (500, 350, 300 and 250) μg/ml. The results of the experiment showed that significant difference in the first group which injected with melittin intra peritoneal 0.2 ml and the second group in mitotic index (MI), where the differences were respectively 8.00 ± 0.56 for the first group and the second group 6.90 ± 0.31. In the case of micro nuclei examination, we also showed significant differences in the third group, where the difference was 14.7 ± 0.29. In the case of micronuclei examination, also there were significant differences in the third group, where the difference was 14.7 ± 0.29.